Rise in carriage of group W meningococci in university students in United Kingdom - Oldfield, Neil J.; Cayrou, Caroline; AlJannat, Mahab A.K.; Al-Rubaiawi, Ali A.A.; Green, Luke R.; Dada, Shehzan; Steels, Oliver D.; Stirrup, Christopher; Wanford, Joe; Atwah, Banan A.Y.; Bayliss, Christopher D.; Turner, David P.J. (Centers for Disease Control and Prevention, 2017)
MenACWY conjugate vaccination was recently introduced in the UK for adolescents and 24 young adults to reduce disease due to Neisseria meningitidis group W (MenW). We 25 conducted a cross-sectional carriage study in first year university students. Despite 71% 26 MenACWY vaccine coverage, carriage of MenW, but not MenY, rose significantly in 27 students.